2011
DOI: 10.1038/oby.2010.245
|View full text |Cite
|
Sign up to set email alerts
|

Respective Contributions of Maternal Insulin Resistance and Diet to Metabolic and Hypothalamic Phenotypes of Progeny

Abstract: Maternal obesity can influence susceptibility to obesity and type 2 diabetes in progeny. We examined the relationship of maternal insulin resistance (IR), a metabolically important consequence of increased adiposity, to adverse consequences of obesity for fetal development. We used mice heterozygous for a null allele of the insulin receptor (Insr) to study the contributions of maternal IR to offspring phenotype without the potential confound of obesity per se, and how maternal consumption of high-fat diet (HFD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
(68 reference statements)
1
37
0
1
Order By: Relevance
“…It is well established that prenatal and immediate postnatal variations in nutrient availability can modulate metabolic status and disease susceptibility in rodents and in humans, but most previous studies have focused on factors that impair adult health, often by increased obesity and impairments in glucose and insulin homeostasis (11,41). A largely separate research tradition has shown that restriction of caloric intake (21,22,28,39,43), or in some cases intake of the amino acid methionine (49), throughout adult life can prevent or delay a wide range of late-life illnesses and thereby increase mean and maximal longevity.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that prenatal and immediate postnatal variations in nutrient availability can modulate metabolic status and disease susceptibility in rodents and in humans, but most previous studies have focused on factors that impair adult health, often by increased obesity and impairments in glucose and insulin homeostasis (11,41). A largely separate research tradition has shown that restriction of caloric intake (21,22,28,39,43), or in some cases intake of the amino acid methionine (49), throughout adult life can prevent or delay a wide range of late-life illnesses and thereby increase mean and maximal longevity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is well established that maternal HFD is a major trigger for long-term deleterious effects on progeny body weight and metabolism (152). HFD increases protein, cholesterol, and triglyceride content in breast milk, elevating total caloric and fat intake in nursing pups (153).…”
Section: Early-life Environmental Regulation Of Adult Metabolismmentioning
confidence: 99%
“…Maternal high-fat diet affects neuropeptide expression in offspring brain regions that control energy homeostasis and affective states (12). In addition, maternal hyperinsulinemia, even in the absence of obesity, influences the differentiation of critical neuronal lineages regulating food intake and energy expenditure (13). To date, among the missing pieces of the puzzle has been the question of how changes in placental gene expression are conveyed to the developing fetus to influence formation and function of neuronal circuits.…”
Section: Fetal Consequences Of Perturbations In Maternal Metabolismmentioning
confidence: 99%